Analysis and testing of the detection performance of an ultra-deep azimuthal electromagnetic logging-while-drilling tool - Yuan, Xiyong; Yang, Zhen; Hou, Shugang; Deng, Shaogui; Qiao, Ping (Frontiers in Earth Science, 2025)
With the increasing complexity of hydrocarbon reservoirs, there is growing demand for greater depth of detection (DoD) in electromagnetic (EM) logging-while-drilling (LWD) tools. The latest generation of ultra-deep azimuthal resistivity LWD systems can reach several tens of meters, enabling precise geosteering, reservoir-scale geological understanding, and optimized field development. This study introduces a newly developed ultra-deep azimuthal EM LWD instrument. Sensitivity analysis of multi-component induced electromotive force (EMF) was performed with respect to resistivity and formation boundaries, identifying the most effective components for boundary detection. Measurement modes were then constructed to separate resistivity and boundary-sensitive signals. Transmitter–receiver spacing and operating frequency were optimized by jointly considering signal dynamics and gain, yielding an optimal range of 5–7 m spacing and 10–50 kHz frequency. A quantitative method was established to characterize maximum boundary-detection capability by integrating signal dynamic range (DR) and system measurement error. Under 80 dB DR and ±5% error, the tool achieved a DoD of 36.4 m. To validate performance, an airhang test model was developed, and finite element simulations were conducted to define test conditions by accounting for shoreline and crane interference. Airhang verification tests are conducted with the instrument parallel to the sea surface. And the measurement results show good agreement with the numerical simulation results. The instrument’s actual DoD exceeds 30 m, representing a significant improvement compared to conventional LWD azimuthal resistivity tool, confirming its value for deep boundary detection in complex geological environments.